Enhancing Radiocarbon Chronologies of Colonization: Chronometric Hygiene Revisited. Issue 2 (18th January 2019) - Schmid, Magdalena M E; Wood, Rachel; Newton, Anthony J; Vésteinsson, Orri; Dugmore, Andrew J
ABSTRACT: Accurately dating when people first colonized new areas is vital for understanding the pace of past cultural and environmental changes, including questions of mobility, human impacts and human responses to climate change. Establishing effective chronologies of these events requires the synthesis of multiple radiocarbon ( 14 C) dates. Various "chronometric hygiene" protocols have been used to refine 14 C dating of island colonization, but they can discard up to 95% of available 14 C dates leaving very small datasets for further analysis. Despite their foundation in sound theory, without independent tests we cannot know if these protocols are apt, too strict or too lax. In Iceland, an ice core-dated tephrochronology of the archaeology of first settlement enables us to evaluate the accuracy of 14 C chronologies. This approach demonstrated that the inclusion of a wider range of 14 C samples in Bayesian models improves the precision, but does not affect the model outcome. Therefore, based on our assessments, we advocate a new protocol that works with a much wider range of samples and where outlying 14 C dates are systematically disqualified using Bayesian Outlier Models . We show that this approach can produce robust termini ante quos for colonization events and may be usefully applied elsewhere.